Letter from Professor Roemer to James Curtis Booth - Roemer, H. (1860)
Roemer write to James Curtis Booth (1810-1888) to announce his receipt of a box of minerals with brucite crystals & the return of another box with Clausthal specimens.
Keywords: Booth, James Curtis, 1810-1888; Brucite; Germany--Clausthal-Zellerfeld